Optimasi dan Analisis Distribusi BBM Menggunakan Metode Saving Matrix, Nearest Insert, dan Nearest Neighbor Pada Multi Compartment Vehicle Routing Problem (MCVRP) - Syahrul Heru Maulana; Suseno Suseno (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Fuel distribution requires efficient route planning to minimize distance, time, fuel consumption, and operational costs. This study optimizes fuel distribution at PT Elnusa Petrofin Integrated Terminal Dumai using the Multi-Compartment Vehicle Routing Problem (MCVRP) combined with Saving Matrix, Nearest Neighbor, and Nearest Insert methods for 30 gas stations served by 16 KL and 24 KL tank trucks.The existing system generated 30 routes with a total distance of 4,001.9 km and a cost of IDR 27,823,768.50. All methods improved efficiency, with Nearest Neighbor providing the best results by reducing routes to 21 and decreasing distance by 24.74%, time by 24.76%, fuel consumption by 5.03%, and cost by 5.05%. Thus, Nearest Neighbor is recommended as the most effective optimization approach.